Worldwide burden of HIV in transgender women: a systematic review and meta-analysis. - Baral, Stefan D; Poteat, Tonia; Strömdahl, Susanne; Wirtz, Andrea L; Guadamuz, Thomas E; Beyrer, Chris (The Lancet infectious diseases, 2013)
Previous systematic reviews have identified a high prevalence of HIV infection in transgender women in the USA and in those who sell sex (compared with both female and male sex workers). However, little is known about the burden of HIV infection in transgender women worldwide. We aimed to better assess the relative HIV burden in all transgender women worldwide.
Keywords: Asia; Developed Countries; Developing Countries; El Salvador; Female; HIV Infections; Humans; Italy; Netherlands; Prevalence; South America; Spain; Transgendered Persons; United States; World Health